Factores criminógenos que inciden en la reincidencia de los sentenciados en delitos de tráfico ilícito de sustancias sujetas a fiscalización - Enderica Guin, César Alberto (2020)
In Ecuador, drug trafficking has become one of the main crimes of crime, thus being one of the most judicialized crimes in the city of Guayaquil and sometimes generating recidivism, which makes up the need to visualize the impact of the sentences deprived of liberty over the course of the process of resocialization of the offender where the lack of policies to prevent recidivism is questioned. This paper describes the criminogenic factors that affect recidivism in sentences for the crime of drug trafficking in a minimum and medium scale in the city of Guayaquil, Ecuador, which was framed in a doctrinal study that involves conducting analysis and interpretation of the information in accordance with the sources consulted for it….